2011
DOI: 10.3109/00952990.2010.540279
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic drug interactions and adverse consequences between psychotropic medications and pharmacotherapy for the treatment of opioid dependence

Abstract: Several interactions between methadone, buprenorphine, or naltrexone and psychoactive medications are described and may have important clinical consequences. To optimize care, clinicians must be alerted to these interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 118 publications
1
36
0
Order By: Relevance
“…Fluoxetine and paroxetine are antidepressants that are regularly prescribed to children with depression. Animal and human research has shown that these can reduce the rate of metabolism of BZD, 34 and in one recent animal study the combination of fluoxetine and BZD actually reversed fluoxetine's anxiogenic effects. 35 These findings, and the observation that a significant proportion of children on BZD are also being prescribed antidepressants, suggest that an examination of the interactive effects of BZD and other psychotropic drugs are an important area of further investigation in paediatric prescribing.…”
Section: Concomitant Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoxetine and paroxetine are antidepressants that are regularly prescribed to children with depression. Animal and human research has shown that these can reduce the rate of metabolism of BZD, 34 and in one recent animal study the combination of fluoxetine and BZD actually reversed fluoxetine's anxiogenic effects. 35 These findings, and the observation that a significant proportion of children on BZD are also being prescribed antidepressants, suggest that an examination of the interactive effects of BZD and other psychotropic drugs are an important area of further investigation in paediatric prescribing.…”
Section: Concomitant Medicationsmentioning
confidence: 99%
“…A study in Japan found that 60% of patients who presented with major depression were prescribed a combination of BZD and antidepressants on their first psychiatric visit. 34 In spite of high rates of coprescribing, the efficacy of combined antidepressants and BZD in the treatment of psychiatric symptoms has not been established.…”
Section: Concomitant Medicationsmentioning
confidence: 99%
“…Dangers include altered metabolism of either medication, methadone overdose, and opioid withdrawal syndromes. Awareness of these interactions is critical (37).…”
Section: Pharmacological Optionsmentioning
confidence: 99%
“…Second, these studies focus on single drug-drug interactions; however, the patient is frequently taking several medications that have not been studied when ingested simultaneously. This is particularly an issue for patients on methadone/buprenorphine given the high prevalence of psychiatric co-morbidity and possible interactions between psychotropic medications and methadone/buprenorphine [14,198]. Third, these studies typically exclude patients with many of the common abnormalities that HIV/HCV patients experience such as hepatic and renal impairments.…”
Section: Clinical Management Of Opioid Withdrawal or Excessmentioning
confidence: 99%